2020
DOI: 10.1111/cxo.12988
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive optics imaging of the retinal microvasculature

Abstract: The eye has long been recognised as the window to pathological processes occurring in the brain and other organs. By imaging the vasculature of the retina we have improved the scientific understanding and clinical best practice for a diverse range of conditions, ranging from diabetes, to stroke, to dementia. Mounting evidence suggests that damage to the smallest and most delicate vessels in the body, the capillaries, is the first sign in many vasculopathies. These are the most critical vessels involved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 92 publications
1
15
0
Order By: Relevance
“…Through the use of the SMART method, all capillaries, independently on their orientation, present an optimal contrast [see Fig. 4(b)], which could be extremely helpful when measuring the wall-to-lumen ratio and other important vessel-based biomarkers [16]. Although not shown here, the SMART method might also improve contrast of generated perfusion maps using off-axis detection methods [4].…”
mentioning
confidence: 99%
“…Through the use of the SMART method, all capillaries, independently on their orientation, present an optimal contrast [see Fig. 4(b)], which could be extremely helpful when measuring the wall-to-lumen ratio and other important vessel-based biomarkers [16]. Although not shown here, the SMART method might also improve contrast of generated perfusion maps using off-axis detection methods [4].…”
mentioning
confidence: 99%
“…Several AO systems and imaging modalities allowed for exquisite visualization of blood vessel wall, lumen and blood cells, enabling the assessment of vascular morphology and perfusion (51). Arteriolar wall thickness and lumen diameter can be measured reliably from AO images (Figure 4) (52).…”
Section: Retinal Vasculaturementioning
confidence: 99%
“…The largest retinal vessels can be accessed non-invasively at a high resolution with optical imaging technology. Retinal blood vessels share structure and function with the heart and cerebral vasculature, making them an interesting non-invasive proxy for coronary artery disease and stroke 3,14 . Previous studies indicated that microstructural alterations in retinal arteries (manifested as vessel wall rigidity, an increase in their stiffness and loss of smooth muscle layer) may be linked to hypertension 15 .…”
Section: Introductionmentioning
confidence: 99%